ANALISIS ALIRAN UDARA PADA JEMBATAN SURAMADU DENGAN MENGGUNAKAN METODE VOLUME HINGGA - Aprianto, Dody Dwi; Fatahillah, Arif; Setiawani, Susi (Kadikma, 2014)
Abstract.This study was aimed to determine the air flow on the Suramadu bridge during extreme conditions. Computational Fluid Dynamics (CFD) is the science study of the flow fluida where air flow is one of them. The wind velocity data that will be examined in this study derived from the previous research. The other data, namely density, viscosity, gravity and pressure obtained from Wikipedia etc. The results of this study in the form of the mathematical model for air flow in the Suramadu bridge obtained using the vinite volume methods. The model was discretized by using upwind Quadratic Interpolation Convective Kinematics (QUICK) to obtain a matrix of size n x n that will be solved by using iterative cojugate gradient methods using MATLAB and Fluent programs. The resulth show that air velocity of Suramadu bridge is extreamly high. It dengerous for any vehicles through the bridge. Key Words: Mathematical Models, Finite Volume Methode, Computational Fluid Dynamics (CFD), Fluent, MATLAB, Discretization.